Antireflective subwavelength structures on microlens arrays—comparison of various manufacturing techniques - Pacholski, Claudia; Spatz, Joachim P. (Applied optics, 2011)
Antireflective subwavelength structures (ARS) resembling nanostructures found on the cornea of night-active insects reduce the reflection of light by providing a gradual change in the refractive index at the interface. These artificial ARS have mainly been fabricated by a combination of conventional lithography and reactive ion etching, which constrains their application to planar substrates. We report on the fabrication of ARS using three different techniques including bottom-up and top-down methods as well as their combination on microlens arrays (MLAs) made of fused silica. The optical performance of the resulting ARS on the MLAs is as good as ARS fabricated on planar substrates with increased transmission of up to 96% at certain wavelengths.